История России: 1917-2004 : учебное пособие / А. С. Барсенков, А. И. Вдовин - Барсенков Александр Сергеевич (Аспект-пресс, 2006)
Экземпляры: Ч/з (20090203) / Инвентарный номер: 93306 / Цена: 300.96 / Сис.шифр: 63.3(2)6 / Авт.знак: Б 26 / ГРНТИ: 03 / ББК: 63.3(2)